Arnica Tincture Cures Cutaneous Leishmaniasis in Golden Hamsters (2018)
ABSTRACT: In search for potential therapeutic alternatives to existing treatments for cutaneous Leishmaniasis, we have investigated the effect of Arnica tincture Ph. Eur. (a 70% hydroethanolic tincture prepared from flowerheads of Arnica montana L.) on the lesions caused by infection with Leishmania braziliensis in a model with golden hamsters. The animals were treated topically with a daily single dose of the preparation for 28 days. Subsequently, the healing process was monitored by recording the lesion size in intervals of 15 days up to day 90. As a result, Arnica tincture fully cured three out of five hamsters while one animal showed an improvement and another one suffered from a relapse. This result was slightly better than that obtained with the positive control, meglumine antimonate, which cured two of five hamsters while the other three showed a relapse after 90 days. This result encourages us to further investigate the potential of Arnica tincture in the treatment of cutaneous Leishmaniasis.